Towards a philosophical foundation of human rights in contemporaneity: Overcoming obstacles in competing views for the legitimization of Human Rights - Piemonte Ditão, Ygor Pierry; Vavá Cavalcante, Antonio; Gobetti, Talissa (Revista de Direito Internacional e Globalização Econômica, 2022)
Using bibliographical review and analysis, this article seeks to elaborate upon the philosophical foundations of Human Rights. In order to do so, we conducted a research regarding the jusnaturalist, positivist, moralist and negationist schools in order to present aspects of converging 'concentric circles'. This structure enables the possibility of a shared philosophical foundation of Human Rights instead of multiple theoretical misconceptions emerging from each theory read individually. There is therefore a lesser risk of leading such theories and their interpretations into anachronism and stasis.